Serum trans£ erases during pregnancy and parturition in Madras red sheep - VISHA, P; LEELA, V; VISWANATHAN, S (The Indian Journal of Animal Reproduction, 2003)
The aspartate aminotransferase (AST) and alanine aminotransferase enzyme (ALT) levels were estimated from the day of mating to the day of parturition at monthly intervals in madras red sheep. Both enzymes showed an increase upto 3rd month and recorded a decrease during 4th month and again recorded increase thereafter.